The SARS-CoV-2 Spike Glycoprotein Biosynthesis, Structure, Function, and Antigenicity: Implications for the Design of Spike-Based Vaccine Immunogens - Duan, Liangwei; Zheng, Qianqian; Zhang, Hongxia; Niu, Yuna; Lou, Yunwei; Wang, Hui (Frontiers in Immunology, 2020)
The ongoing pandemic of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), poses a grave threat to global public health and imposes a severe burden on the entire human society. Like other coronaviruses, the SARS-CoV-2 genome encodes spike (S) glycoproteins, which protrude from the surface of mature virions. The S glycoprotein plays essential roles in virus attachment, fusion and entry into the host cell. Surface location of the S glycoprotein renders it a direct target for host immune responses, making it the main target of neutralizing antibodies. In the light of its essential role in viral infection and adaptive immunity, the S protein is the focus of most vaccine strategies as well as therapeutic interventions. In this review, we highlight and describe the recent progress that has been made in the biosynthesis, structure, function, and antigenicity of the SARS-CoV-2 S glycoprotein, aiming to provide valuable insights into the design and development of the S protein-based vaccines as well as therapeutics.